"This Is What a Feminist Looks Like": Dead Girls and Murderous Boys on Season 1 of Netflix's You. (March 2021) - Rajiva, Mythili; Patrick, Stephanie
The taking up of feminist discourses and practices by a violent misogynist on Netflix's You is an important departure from mainstream televisual engagements with gendered violence. Drawing on Jackson and Mazzei's methodological work, we examine "threshold texts" as those that radically destabilize incommensurable political stances such as feminism/misogyny and queer alliance/homophobia. What are the implications of this destabilization for social justice projects? First, we argue that Joe's voice-over re-centers white, heteronormative masculinity. Second, we examine the implicit homophobia underlying the show's depiction of female friendships as queer danger. Third, we argue the representations of masculinity offer a hopeless landscape for heteronormative female viewers. We conclude by looking at the paratextual context, specifically actor Penn Badgley's own ambivalent location as a queer, feminist man playing a character that represents heteronormativity's deadliest outcome.